Pengaruh Investasi Dan Kualitas Sumber Daya Manusia Terhadap Pemerataan Pendapatan Di Indonesia - Rissa Andriani Erfan; Syamsul Amar B (Universitas Negeri Padang, 2023)
This study aims to : (1) Determine the effect of Domestic Investment on Income Equality in Indonesia. (2) Knowing the influence of Foreign Direct Investment on Income Equality ini Indonesia. (3) Knowing the effect of the quality of human resources on Income Equality in Indonesia. This research is descriptive and associative. The data used in study are documentation data from 30 provinces in Indonesia from 2010 to 2019 which were obtained through the Badan Pusat Statistik. This research was conducted using the panel data regression method with the Random Effect Model (REM). The results of this study indicate that : (1) Domestic Investment has a negative and insignificant effect on Income Equality in Indonesia. (2) Foreign Direct Investment has a positive and significant effect on Income Equality in Indonesia. (3) The Quality of Human Resources has a negative and significant effect on Income Equality in Indonesia.